Effect of lipopolysaccharide-induced immune stimulation and maternal fish oil and microalgae supplementation during late pregnancy on nursery pig hypothalamic–pituitary–adrenal function. (13th May 2019) - You, Lan; Lee, Alison V; Oh, Se-Young; Fisher-Heffernan, Rebecca E; Edwards, Michelle; de Lange, Kees; Karrow, Niel A
Abstract: The present study used Escherichia coli lipopolysaccharide (LPS ) to investigate whether maternal immune challenge during late gestation altered programming of the offspring hypothalamus and hypothalamic–pituitary–adrenal axis (HPAA ). In addition, interactions of maternal diet, supplementation with fish oil (FO ) or microalgae (AL ), and complex vs. simple weaning diets were investigated. Briefly, Landrace × Yorkshire sows ( N = 48) were randomly assigned to diets supplemented with FO, AL, or a standard gestation control diet (CON ) from day 75 of gestation (gd 75) until parturition. On gd 112, half the sows from each dietary treatment were immune challenged with LPS (10 μg/kg BW) or saline as a control. At 21 d postpartum, the offspring were weaned, and half the animals from each maternal treatment were allocated to either a complex or simple weaning diet. At 28 d postpartum, the offspring's hourly fever and 2-h cortisol responses to LPS immune challenge (40 μg/kg BW) were measured to assess hypothalamus and HPAA function. Results indicated that the maternal temperature of sows on the FO diet returned to baseline levels faster than sows on the AL and CON diets after LPS immune challenge ( P < 0.05). In contrast, there was no difference in the maternal cortisol response across the dietary treatments ( P > 0.10). Regardless of the dietary treatments, the maternal LPS immune challenge induced a greater cortisol response in male offspring ( P = 0.05) and a greater fever response in female offspring ( P = 0.03) when they were LPS immune challenged post-weaning. Male offspring from LPS-immune-challenged sows fed the FO and AL diets had a greater fever response than male offspring from the maternal CON diet group ( P ≤ 0.05). Last, no effect of the complex or simple weaning diets was observed for the nursery pig cortisol or fever responses to LPS immune challenge. In conclusion, LPS immune challenge during late pregnancy altered responsiveness of the offspring hypothalamus and HPAA to this same microbial stressor, and a sex-specific response was influenced by maternal dietary supplementation with FO and AL.